2021
DOI: 10.5380/rbclima.v28i0.76268
|View full text |Cite
|
Sign up to set email alerts
|

Padrões Climatológicos Associados a Eventos De Seca No Leste Do Estado De São Paulo

Abstract: Os mecanismos de ocorrência de secas no Sudeste do Brasil são complexos, pois a região encontra-se em uma zona de transição entre os regimes atmosféricos tropical e extratropical. Este trabalho apresenta as condições climatológicas médias sazonais no início de eventos de seca na faixa leste do estado de São Paulo no período de 1901 a 2010. Estes eventos foram identificados utilizando o índice de evapotranspiração-precipitação padronizado (SPEI) calculado a partir dos dados da reanálise ERA20C. Durante o verão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(50 reference statements)
0
5
0
3
Order By: Relevance
“…In the winter, surface anticyclonic circulation predominates at MASP, and postfrontal high-pressure systems moving northeast typically merge with SASA. This winter synoptic pattern inhibits cloud formation and provides increased atmospheric stability, leading to a higher frequency of thermal inversions and restrictions on the air pollutant dispersion at MASP (Piñero Sánchez et al, 2020;Gozzo et al, 2021;Oliveira et al, 2021).…”
Section: Methodology Characterization Of the Study Areamentioning
confidence: 99%
“…In the winter, surface anticyclonic circulation predominates at MASP, and postfrontal high-pressure systems moving northeast typically merge with SASA. This winter synoptic pattern inhibits cloud formation and provides increased atmospheric stability, leading to a higher frequency of thermal inversions and restrictions on the air pollutant dispersion at MASP (Piñero Sánchez et al, 2020;Gozzo et al, 2021;Oliveira et al, 2021).…”
Section: Methodology Characterization Of the Study Areamentioning
confidence: 99%
“…Under the SASA in winter, SEB experiences weather with clear skies, weak winds, and subsidence movements, the blocking of the synoptic system's passage and inhibition of cloud formation, and developing thermal inversions in the atmosphere. All these conditions are unfavorable to the dispersion of pollutants in the most urbanized Brazilian region [192,193].…”
Section: Cluster 5-region 5 (R5)mentioning
confidence: 99%
“…The onset of a drought episode can be identified when the SPI changes from a positive to a negative value, and it ends when the index returns to a positive value; however, to define the event as dry, the SPI must reach a value less than or equal to −1 [17]. Works such as Gozzo et al [52], Stojanovic et al [88] and Drumond et al [89] also applied a similar methodology to assess the onset of events in order to include the mild dry conditions that lead to the establishment of a drought in the analysis. In addition to the criteria to define a drought, McKee et al [17] created a system to classify the SPI values, as shown in Table 1.…”
Section: Identification Of Dry Periodsmentioning
confidence: 99%
“…Usually, droughts in the NEB are mainly associated with (a) the occurrence of the warm phase of the El Niño Southern Oscillation (ENSO) phenomenon, resulting from an anomalous warming of the surface of the Tropical Pacific sea, which causes changes in the Walker zonal circulation cell, negatively impacting precipitation in the NEB [42][43][44][45] and (b) part of the rainfall variability is explained by warming in the North Tropical Atlantic Ocean, which results in an anomalous position further north of the Intertropical Convergence Zone (ITCZ) compared to its climatological position [45][46][47][48][49][50][51]. The SEB is located in the transition region of the tropical and extratropical atmospheric regimes and presents complex drought mechanisms, which affect weather patterns and, consequently, the rainfall [52]. The severe drought of 2014/2015, for instance, was associated with an anomalous convective activity in the region of Australia that triggered the action of an anomalous high atmospheric pressure system over the warmer South Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%